2007
DOI: 10.1088/0029-5515/47/8/036
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal and poloidal momentum transport studies in JET

Abstract: This paper reports on the recent studies of toroidal and poloidal momentum transport in JET. The ratio of the global energy confinement time to the momentum confinement is found to be close to τ E /τ φ =1 except for the low density discharges where the ratio is τ E /τ φ =2-3. On the other hand, local transport analysis of tens of discharges shows that the ratio of the local effective momentum diffusivity to the ion heat diffusivity is χ φ /χ i 0.1-0.4 rather than unity, as expected from the global confinement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 42 publications
5
47
1
Order By: Relevance
“…These behaviors give some confidence in the veracity of the poloidal velocity measurements. The measured poloidal velocity profiles on NSTX are equal to or lower in magnitude than expected from neoclassical calculations from NCLASS and GTC-Neo, in contrast to measurements on JET and DIII-D. [2][3][4] Differential changes in measured mean poloidal velocity are seen to be a factor of 2.6-3.3 lower than changes in NCLASS and GTC-Neo. There is no indication of an inconsistency with the direction of the measured poloidal velocity compared to neoclassical expectations, as was observed on DIII-D. 4 These results are consistent with measurements on MAST with showed that, within experimental error, the measured poloidal flow was similar to neoclassical values in magnitude and direction.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These behaviors give some confidence in the veracity of the poloidal velocity measurements. The measured poloidal velocity profiles on NSTX are equal to or lower in magnitude than expected from neoclassical calculations from NCLASS and GTC-Neo, in contrast to measurements on JET and DIII-D. [2][3][4] Differential changes in measured mean poloidal velocity are seen to be a factor of 2.6-3.3 lower than changes in NCLASS and GTC-Neo. There is no indication of an inconsistency with the direction of the measured poloidal velocity compared to neoclassical expectations, as was observed on DIII-D. 4 These results are consistent with measurements on MAST with showed that, within experimental error, the measured poloidal flow was similar to neoclassical values in magnitude and direction.…”
Section: Discussioncontrasting
confidence: 55%
“…Some recent measurements of poloidal velocity differ by an order of magnitude with neoclassical predictions: on JET in the region of an internal transport barrier (ITB) 2,3 , and on DIII-D during H-mode and quiescent H-mode discharges 4 , where the direction of the poloidal flow also differed from the neoclassical expectation. Measurements of poloidal flow on JT-60U…”
Section: Introductionmentioning
confidence: 88%
“…16 As noted previously, rapid poloidal rotation has been observed to be correlated with internal transport barriers in several tokamaks, including JET. 10,28 The highest poloidal velocities recorded in this device, 75Ϯ 20 km s −1 ͑in the ion diamagnetic direction͒, were measured inside a transport barrier in shot number 58094; immediately outside the barrier, the poloidal velocity measurement was consistent with zero. Between these two radial locations, respectively, at R Ӎ 3.34 m and R Ӎ 3.46 m, the ion temperature was observed to drop from about 20 to about 7 keV, while the electron density dropped by approximately a factor of two, the local safety factor q being close to 2 at both locations.…”
Section: Discussionmentioning
confidence: 73%
“…1. The worldwide progress in understanding the physics of momentum transport and rotation has been made both experimentally [9][10][11][12][13][14][15][16][17][18][19][20] and theoretically [21][22][23][24][25]. As for the elements determining V t , the characteristics of momentum transport, which consists of diffusive (toroidal momentum diffusivity, χ φ ) and non-diffusive (convection velocity, V conv ) terms [10,14,18], the external momentum input, author's e-mail: yoshida.maiko@jaea.go.jp and the intrinsic rotation [15,17,19,23] have been reported individually.…”
Section: Introductionmentioning
confidence: 99%